Influence Mechanism of Cu Layer Thickness on Photoelectric Properties of IWO/Cu/IWO Films - Fengbo Han (Materials, 2019)
Transparent conductive IWO/Cu/IWO (W-doped In2O3) films were deposited on quartz substrates by magnetron sputtering of IWO and Cu in the Ar atmosphere. The X-ray diffraction (XRD) patterns identified the cubic iron−manganese ore crystal structure of the IWO layers. The influence of the thickness of the intermediate ultra-thin Cu layers on the optical and electrical properties of the multilayer films was analyzed. As the Cu layer thickness increases from 4 to 10 nm, the multilayer resistivity gradually decreases to 4.5 × 10−4 Ω·cm, and the optical transmittance in the mid-infrared range increases first and then decreases with a maximum of 72%, which serves as an excellent candidate for the mid-infrared transparent electrode.